2001
DOI: 10.1029/2000gl012391
|View full text |Cite
|
Sign up to set email alerts
|

Transport of biomass burning smoke to the upper troposphere by deep convection in the equatorial region

Abstract: Abstract. During LBA-CLAIRE-98, we found atmospheric layers with aged biomass smoke at altitudes > 10 km over Suriname. CO, CO2, acetonitrile, methyl chloride, hydrocarbons, NO, 03, and aerosols were strongly enhanced in these layers. We estimate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
182
3
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(212 citation statements)
references
References 23 publications
(15 reference statements)
18
182
3
9
Order By: Relevance
“…The BL is capped by an inversion layer at 3.0 km, which was observed on several flights during the campaign. This so-called trade wind inversion has been reported in different studies on tropical regions and is known to act as an effective transport barrier so that trace species can accumulate in the BL (Schubert et al, 1995;Gouget et al, 1996;Andreae et al, 2001). The vertical profile of CO shows a high mixing ratio of (131.7 ± 10.1) ppbv in the lower troposphere and a slightly lower value of (116.0 ± 4.3) ppbv in the outflow region.…”
Section: Convective Transport Of Ozone-rich Air and The Role Of Entramentioning
confidence: 89%
See 1 more Smart Citation
“…The BL is capped by an inversion layer at 3.0 km, which was observed on several flights during the campaign. This so-called trade wind inversion has been reported in different studies on tropical regions and is known to act as an effective transport barrier so that trace species can accumulate in the BL (Schubert et al, 1995;Gouget et al, 1996;Andreae et al, 2001). The vertical profile of CO shows a high mixing ratio of (131.7 ± 10.1) ppbv in the lower troposphere and a slightly lower value of (116.0 ± 4.3) ppbv in the outflow region.…”
Section: Convective Transport Of Ozone-rich Air and The Role Of Entramentioning
confidence: 89%
“…The formation of ozone eventually becomes less efficient in a high-NO x environment (Liu et al, 1987;Lin et al, 1988). In general, ozone production in convective outflow regions vary over a wide range, from ozone destruction or small net production in remote marine regions (Wang and Prinn, 2000;Mari et al, 2003) to significant net ozone production of several tens of ppbv d −1 in biomass burning plumes transported into the free troposphere (Roelofs et al, 1997;Andreae et al, 2001). …”
mentioning
confidence: 99%
“…Some measurements showed an unexpected increase of trace gas concentrations above 10 km. Employing back trajectories calculations, Andreae et al (2001) concluded that it originated from savanna fires further downwind that were vertically transported by deep convection and brought equatorward by the upper level circulation. Analysis of aerosol size distributions indicated a possible formation of new particles near the detrainment zone of deep convection (Krejci et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burn haze can be transported to high altitudes and undergo long-range transport, hence impacting the global climate. 12,13 Since the CCN activity of organic aerosols depends strongly on the type and concentration of different organic compounds, one of the key factors determining the interplay of direct and indirect effects of biomass burn aerosols on the earth's radiation budget is their chemical composition. The overall climate and environmental effects of increasing atmospheric aerosol concentrations remain largely unknown, primarily due to large uncertainties in the chemical composition of organic aerosols as well as a limited understanding of the chemical transformations and atmospheric lifetimes of particles due to atmospheric processing.…”
Section: Introductionmentioning
confidence: 99%